Adjuvant chemoradiotherapy versus with radiotherapy alone for locally advanced salivary gland carcinoma among older patients. Issue 6 (4th September 2015) - Tanvetyanon, Tawee; Fisher, Kate; Caudell, Jimmy; Otto, Kristen; Padhya, Tapan; Trotti, Andy
Abstract: Background: The majority of patients with locally advanced salivary gland carcinoma will die of the disease even after curative surgery. Few studies on adjuvant therapy have been conducted. In this study, we compared adjuvant chemoradiotherapy (CRT) with adjuvant radiotherapy among the older patient population. Methods: Surveillance, Epidemiology, and End Results (SEER)‐Medicare database (1992–2009) was analyzed. Eligible cases were those receiving curative surgery followed by adjuvant therapy. Outcomes were overall survival and toxicity. Results: Analyses included 741 patients: 641 patients (86.5%) received adjuvant radiotherapy and 100 (13.5%) received adjuvant CRT. The median overall survival was 41.0 months with adjuvant radiotherapy and 24 months with CRT. Both multivariable and propensity score‐adjusted analyses indicated that adjuvant CRT was associated with an increased mortality (hazard ratio [HR]: 1.39; 95% confidence interval [CI]: 1.07–1.79 and HR: 1.49; 95% CI: 1.14–1.94, respectively). Toxicity rates were significantly higher in the CRT group. Conclusion: Treatment with adjuvant CRT was associated with an increased mortality and toxicity when compared to adjuvant radiotherapy alone. © 2015 Wiley Periodicals, Inc. Head Neck 38: 863–870, 2016